Range distribution extension of Asthenes sclateri (Aves: Furnariidae) in Peru - Servat, Grace P. (2008)
We extent the distribution range in Peru of Asthenes sclateri, Cabanis (“Puna Canastero”), a species reported only for the Puno Department. The observations of many individuals of the species (documented with pictures and specimens) were made in high Andean pastures nearby Polylepis woodlands in the Arequipa Department.